2018
DOI: 10.3390/ma11081322
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PLA Filament Conditions on Characteristics of FDM Parts

Abstract: Additive manufacturing technologies play an important role in Industry 4.0. One of the most prevalent processes is fused deposition modelling (FDM) due to its versatility and low cost. However, there is still a lack of standardization of materials and procedures within this technology. This work aims to study the relationship of certain operating parameters and the conditions of poly(lactic acid) (PLA) polymer with the results of the manufactured parts in dimensional terms, surface quality, and mechanical stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 17 publications
2
115
0
3
Order By: Relevance
“…The results of this study agree with the findings of Galantucci et al [34] that printing speed is the most effective process parameter determining dimensional accuracy. Valerga et al [30] have affirmed the negative influence of high printing temperatures on dimensional accuracy. The results of Sood et al [35] agree only in part with this study, since they recommended greater layer thickness to reduce percentage deviation.…”
Section: Dimensional Accuracymentioning
confidence: 95%
See 2 more Smart Citations
“…The results of this study agree with the findings of Galantucci et al [34] that printing speed is the most effective process parameter determining dimensional accuracy. Valerga et al [30] have affirmed the negative influence of high printing temperatures on dimensional accuracy. The results of Sood et al [35] agree only in part with this study, since they recommended greater layer thickness to reduce percentage deviation.…”
Section: Dimensional Accuracymentioning
confidence: 95%
“…Yang et al [32] and Pérez et al [28] confirmed the low impact of printing temperature, if it is considered independently from the other parameters. Valerga et al [30] validated only the negative influence of high printing temperature, but the interaction between temperature and layer thickness was not examined. However, this investigation has shown that high temperature, when combined with thin layers, decreases the surface roughness, but the influence of printing temperature on surface roughness in general is only marginal.…”
Section: Surface Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Raju et al [19] also showed that layer thickness and build orientation were two significant parameters for surface quality. Valerga et al [62] analyzed various PLA filament conditions to know their impact on surface quality, along with the dimensional accuracy and tensile strength of the FDM printed part. They considered extrusion temperature, humidity, and pigmentation color as variables.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…In connection with [93] where increased humidity has been proven to enhance particle size growth, adjustment of humidity within the printing workspace may be an approach to promoting the growth of emitted particles to less hazardous larger agglomerates, although sustaining high humidity may present practical issues. 3D printing filament printability and print operation can be adversely affected by the presence of moisture in the air [127]. This could be a low priority measure, employed in cases where multiple printers need to be operated and further risk mitigation is required.…”
mentioning
confidence: 99%